The History of the Diadochoi in Book XIX of Diodoros' "Bibliotheke": a historical and historiographical commentary - Meeus, Alexander (Untersuchungen zur antiken Literatur und Geschichte, 2022)
Frontmatter -- Preface -- Contents -- Introduction -- Part I: Diodoros and His Work -- 1 Diodoros of Agyrion -- 2 The Bibliotheke -- 3 The Problem of the Sources -- 4 The Chronology of the Years 317-311 -- Part II: Commentary -- § 2.1 Chronographic Formula for the Year 317/6 -- § 11 Olympias' Return, the Deaths of Arrhidaios and Eurydike, and Olympias' Revenge on the Antipatrids for the Death of Alexander -- § 12-13 Eumenes in Babylonia and the Crossing of the Tigris -- § 14 Eumenes' Alliance with the Governors and Generals from the Upper Satrapies -- § 15 The Power Struggle of the Commanders of the Satrapal Alliance and the Alexander Tent -- § 16 The End of the Perdikkan Captives -- § 17-19 Antigonos' Crossing into the Upper Satrapies and the First Skirmishing -- § 20 Rest, Recovery and Replenishment in Media -- § 21-24 The Struggle for Power in the Satrapal Coalition Surfaces Again -- § 25-26 The Prelude to the Battle of Paraitakene -- § 27-31 The Battle of Paraitakene -- § 32 The Aftermath of the Battle -- § 33-34 Keteus' Widows Compete to Join Their Husband in Death -- § 35-36 Kassandros' Return to Macedonia and the Struggle against Polyperchon and Olympias -- § 37-39 The Build Up to the Battle of Gabiene -- § 40-43 The Battle of Gabiene -- § 44 The Aftermath of the Battle -- § 45 The Flood of Rhodes -- § 46-48 The Establishment of Antigonos' Supremacy in Asia -- § 49-51 The Defeat and Death of Olympias -- § 52-54 The Establishment of Kassandros' Power in Europe -- § 55-57 Seleukos' Flight and the Coalition against Antigonos -- § 58-60 Antigonos' Preparations for the War and the Siege of Tyre -- § 61 Antigonos' Propagandistic Proclamation at Tyre -- § 62 The Reaction of Ptolemaios -- § 63-64 The First Phase of the War in Europe and the Aegean -- § 66-69 The Second Year of the War -- § 73-75 The Third Year of the War -- § 77-78 Polemaios in Greece -- § 79 Ptolemaios' Interventions in Kyrene and Cyprus, and the Raids on the Syrian and Kilikian Coasts -- § 80-84 The Battle of Gaza -- § 85-86 The Aftermath of the Battle -- § 87 Telesphoros' Revolt in the Peloponnese -- § 88-89 Kassandros' Operations in Epeiros and Illyria -- § 90-92 Seleukos' Return to Babylon -- § 93 Ptolemaios' Loss of Syria -- § 94-100.2 The Antigonid Campaigns against the Nabataians -- § 100.3-7 Demetrios' Expedition in Babylonia -- § 105.1-4 The Peace of the Dynasts and the Deaths of Alexander IV and Rhoxane -- Abbreviations -- Bibliography -- Appendix: Textual Variants -- Index Graecitatis